Problematika Pembentukan Undang-Undang Cipta Kerja Terkait Perlindungan Terhadap Hak-Hak Tenaga Kerja di Indonesia - Hermawati, Mutiara; S, Suwarsit (Media Hukum Indonesia (MHI), 2024)
The main urgency of the establishment of the Job Creation Law is aimed at improving and stimulating the growth of the Indonesian economy through increased investment and expansion of employment. However, after the draft law has been completed and will be ratified, the contents of the articles regulated therein contain an imbalance between employers and labor. Where employers are considered to have many advantages in the regulation and on the other hand the rights of labor are increasingly trimmed and restricted. So that at the stage of ratification, the law reaped polemics and controversy among the community. With this problem, this research was conducted by the author with the aim of finding out about the causes of the controversial Job Creation Law and the impact it has on labor. The method used in this research is the literature method which uses secondary data sources by collecting data through various reading sources such as articles, journals, papers, and news. The result of this research is that to ease the controversy, the Job Creation Law was submitted to the Constitutional Court to pass the material and formal testing stages until the result obtained was that the law was declared Conditionally Unconstitutional.